Morphometric Variations And Corbicula Javanica Growth Patterns In Halang Island Waters, Rokan Hilir District - Muhammad Mansur; Efawani Efawani; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis research was conducted in Halang Island waters, Rokan Hilir Regency in May-June 2019. The study aims to find out the morphometric variations and also the growth patterns of the mussel shells. Purposive sampling method was used in this research to determine the location of the sampling. The mussel shells sample obtained from the three stations were 506 individuals (station I were 161 individuals, station II were 175 individuals, station III were 170 individuals). There were 5 characteristics of morphometric examined in each male and female sample, namely PL, LBC, LC, TEC, and BT. From the research results the length-weight relation shown that the growth patterns of mussel shells was negative allometric (3 > 0.041).Keywords: Variation, Corbicula Javanica, Halang Island, Growth Pattern.